Opercularella - Galea, Horia R.; Schories, Dirk (Zenodo, 2012)
Opercularella sp. (Fig. 2 D) Material examined . Stn. RAS — 19.ii.2010, Ant.04/2010 (43 m): sterile colonies epizoic on Antarctoscyphus spiralis (MHNG-INVE-79793); Ant.14/2010 (43 m): sterile colony on plumose bryozoan (MHNG-INVE-79789). Description . Hydrorhiza reptant, giving off pedicellate hydrothecae at irregular intervals. Pedicels slender (50–70 µm wide) and of varied length (155–730 µm), either unbranched or sparingly and irregularly branched once or twice; perisarc spirally grooved, slightly widening distally and merging smoothly into hydrotheca; pedicel and hydrotheca delimited by delicate "diaphragm". Hydrothecae 360–560 µm long, lateral walls slightly divergent, widest (110–160 µm) at opercular base; operculum membranous, conical, pleated, not delimited basally by crease line. Gonothecae absent. Remarks . The sterile condition of the present material prevent us from providing a reliable identification for this species. It may belong to Opercularella belgicae (Hartlaub, 1904), but hydrothecal pedicels of this species appear to be smooth, except for the presence of 2–3 basal, spiral annulations (see Galea 2007). Published as part of Galea, Horia R. & Schories, Dirk, 2012, Some hydrozoans (Cnidaria) from King George Island, Antarctica, pp. 1-21 in Zootaxa 3321 on page 7, DOI: 10.5281/zenodo.213236